2013
DOI: 10.3389/fpsyg.2013.00945
|View full text |Cite
|
Sign up to set email alerts
|

The lognormal handwriter: learning, performing, and declining

Abstract: The generation of handwriting is a complex neuromotor skill requiring the interaction of many cognitive processes. It aims at producing a message to be imprinted as an ink trace left on a writing medium. The generated trajectory of the pen tip is made up of strokes superimposed over time. The Kinematic Theory of rapid human movements and its family of lognormal models provide analytical representations of these strokes, often considered as the basic unit of handwriting. This paradigm has not only been experime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
49
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 58 publications
(57 citation statements)
references
References 102 publications
3
49
0
1
Order By: Relevance
“…As for kinematic models, they generate curvilinear speed profiles reflecting the effect of neuromuscular impulses involved in the generation of motions. Many models have been developed under this approach such as the deltalognormal [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29], the double gaussian [30], the sigma-lognormal [31], the double beta [32]. The problem of kinematic models is the lack of information on the spatial aspect of the movement.…”
Section: Overview Of Some Handwriting Modelsmentioning
confidence: 99%
“…As for kinematic models, they generate curvilinear speed profiles reflecting the effect of neuromuscular impulses involved in the generation of motions. Many models have been developed under this approach such as the deltalognormal [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29], the double gaussian [30], the sigma-lognormal [31], the double beta [32]. The problem of kinematic models is the lack of information on the spatial aspect of the movement.…”
Section: Overview Of Some Handwriting Modelsmentioning
confidence: 99%
“…On the other hand, experimental studies have consistently found that the kinematics of arm movements are highly stereotypical under a large variety of experimental conditions (Engelbrecht 2001). Such a generalization has lead to postulate the underlying existence of a lognormality principle that guides human beings throughout their life, from the early steps of their motor learning processes to increasing departure from the ideal lognormal behavior, as the control of the fine motricity begins to decline with age and illness (Plamondon et al 2013). From a more pragmatic perspective, the Kinematic Theory considers that the velocity is the main control variable used by the central nervous system to generate a handwritten trajectory.…”
Section: Human Control Behaviormentioning
confidence: 99%
“…e tangential speed pro le of point-to-point aiming movements typically assumes a "bell shape" [17,33,38], variably asymmetric depending on the rapidity of the movement [35,39]. It is generally accepted that complex movements can be described with the superimposition of a discrete number of basic "ballistic" primitives o en referred to as strokes [34,41,43], which are also characterised by bell shaped velocity pro les.…”
Section: Introductionmentioning
confidence: 99%
“…It is generally accepted that complex movements can be described with the superimposition of a discrete number of basic "ballistic" primitives o en referred to as strokes [34,41,43], which are also characterised by bell shaped velocity pro les. With experience, a movement tends to become smoother [39][40][41] and the number of velocity peaks decreases. is phenomenon is known as co-articulation and can be interpreted as the chunking of movement primitives at the planning level [41].…”
Section: Introductionmentioning
confidence: 99%